2021
DOI: 10.1371/journal.pgen.1009663
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans RMI2 functional homolog-2 (RMIF-2) and RMI1 (RMH-1) have both overlapping and distinct meiotic functions within the BTR complex

Abstract: Homologous recombination is a high-fidelity repair pathway for DNA double-strand breaks employed during both mitotic and meiotic cell divisions. Such repair can lead to genetic exchange, originating from crossover (CO) generation. In mitosis, COs are suppressed to prevent sister chromatid exchange. Here, the BTR complex, consisting of the Bloom helicase (HIM-6 in worms), topoisomerase 3 (TOP-3), and the RMI1 (RMH-1 and RMH-2) and RMI2 scaffolding proteins, is essential for dismantling joint DNA molecules to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…We will refer to the new top-3 allele, jf153 , as top-3-ZnF . We also inserted an internal HA tag into both the wt and top-3-ZnF alleles, as previously described ( 16 ). Western blot analysis showed that the truncated protein is expressed at similar levels to the wt (Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We will refer to the new top-3 allele, jf153 , as top-3-ZnF . We also inserted an internal HA tag into both the wt and top-3-ZnF alleles, as previously described ( 16 ). Western blot analysis showed that the truncated protein is expressed at similar levels to the wt (Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The recombination frequency and CO number and position in wt, top-3-ZnF and rmh-2(jf168) were determined as previously described ( 16 ) using the C. elegans Hawaiian and Bristol hybrid strains. Specifically, we injected the mutation of interest into the Hawaiian strain and subsequently crossed it with the same mutation in the Bristol strain to generate the Hawaiian/Bristol hybrid.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations